2018
DOI: 10.1158/0008-5472.can-17-2118
|View full text |Cite
|
Sign up to set email alerts
|

E6 Protein Expressed by High-Risk HPV Activates Super-Enhancers of the EGFR and c-MET Oncogenes by Destabilizing the Histone Demethylase KDM5C

Abstract: The high-risk (HR) human papillomaviruses (HPV) are causative agents of anogenital tract dysplasia and cancers and a fraction of head and neck cancers. The HR HPV E6 oncoprotein possesses canonical oncogenic functions, such as p53 degradation and telomerase activation. It is also capable of stimulating expression of several oncogenes, but the molecular mechanism underlying these events is poorly understood. Here, we provide evidence that HPV16 E6 physically interacts with histone H3K4 demethylase KDM5C, result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 47 publications
1
35
0
Order By: Relevance
“…In line with the oncogenic roles of KDM5A and KDM5B, suppression of KDM5A or KDM5B delays tumor formation, metastasis, and drug resistance in breast, lung, melanoma, and gastric cancers [ 17 , 21 29 ]. Although inhibition of KDM5C could have adverse effects on neuronal circuits [ 62 ] or promote tumor formation in clear cell renal carcinoma [ 63 ] and cervical cancer [ 64 ], KDM5C was also shown to have oncogenic roles in prostate cancer [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with the oncogenic roles of KDM5A and KDM5B, suppression of KDM5A or KDM5B delays tumor formation, metastasis, and drug resistance in breast, lung, melanoma, and gastric cancers [ 17 , 21 29 ]. Although inhibition of KDM5C could have adverse effects on neuronal circuits [ 62 ] or promote tumor formation in clear cell renal carcinoma [ 63 ] and cervical cancer [ 64 ], KDM5C was also shown to have oncogenic roles in prostate cancer [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…KDM5C has also been observed to be overexpressed and promote tumor growth in prostate cancer ( 14 ). In contrast, KDM5C plays a tumor-suppressing role in cervical cancer, breast cancer and renal carcinoma ( 15 17 ). Nevertheless, the exact effect of KDM5C on ICC is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…They are potent mediators of communication between cancer cells and their surrounding microenvironment, which contains various types of host cells, including HUVECs [16][17][18][19][20][21][22][23]35]. Given that E6 oncoproteins are the critical drivers of HPV 16/18-associated CC development [36,37], we hypothesized that HPV 16/18 E6 in uences the TME via EVs. As expected, we observed that EVs derived from the four HPV 16/18 E6-KD cell lines and corresponding control cells were effectively internalized by HUVECs.…”
Section: Discussionmentioning
confidence: 99%